Hepatocellular Carcinoma with Osteoclast-Like Giant Cells: Report of the Seventh Case in the Literature - Lorenzo Dioscoridi; Damiano Bisogni; Giancarlo Freschi (Case Reports in Surgery)
Hepatocellular carcinoma with osteoclast-like giant cells is extremely rare, and only six cases have been previously reported. Its histogenesis is at the moment controversial. The authors report a case of hepatocellular carcinoma with osteoclast-like giant cells found in a 74-year-old woman. The patient came with a dull pain in the right upper abdominal quadrants due to a liver neoplasm described at CT scan. A wedge resection of the fifth hepatic segment with appendectomy, omentectomy, and debulking of the major peritoneal implants was performed. Histologically, the diagnosis of hepatocellular carcinoma with high grade differentiation associated with giant osteoclast-like cells was done without any evidence of hepatitis or cirrhosis in the surrounding hepatic parenchyma. Immunohistochemistry was positive for CD10 and CD68 and in situ hybridization revealed the expression of receptor activator of nuclear factor-kappa B (RANK) in the giant cells and receptor activator of nuclear factor-kappa B ligand (RANKL) in the tumor cells.